PERUBAHAN PERILAKU KONSUMEN GENERASI MILENIAL DAN GENERASI Z TERHADAP PEMBELIAN CONSUMER GOODS PADA ERA DIGITAL DI DESA BETON - Septiana, Elysa; Damanuri, Aji (Fakultas Ekonomi dan Bisnis Universitas Alma Ata, 2024)
Consumer behavior is experiencing major changes as a result of advances in digital technology in the digital economy era. Customers are becoming more involved and knowledgeable in selecting goods and services as their needs become increasingly complex. Changes in consumer behavior from the millennial generation (born around 1981 to 1996) and generation Z (born from 1997 to 2012) have had a significant impact on purchasing consumer goods in the digital era. The consumer goods category is clothing, skincare, toys, food, home décor and household furniture. This research aims to identify changes in the behavior of millennial and generation Z consumers regarding consumer goods purchasing decisions in the digital era in Beton Village. This research is qualitative descriptive field research. The objects of this research are the millennial generation and generation Z in Beton Village. The results of this research are changes in consumer behavior, the millennial generation prefers to shop in physical stores, while generation Z tends to actively buy consumer goods through the online shopping application, namely Shoppee. Generation Z who dominates consumer goods purchases are students.